Integrated Transcriptomics and Metabolomics Analyses Provide Insights Into the Response of Chongyi Wild Mandarin to Candidatus Liberibacter Asiaticus Infection - Peng, Ting; Kang, Jing-Liang; Xiong, Xin-Ting; Cheng, Fang-Ting; Zhou, Xiao-Juan; Dai, Wen-Shan; Wang, Min; Li, Zhong-Yang; Su, Hua-Nan; Zhong, Ba-Lian (Frontiers in Plant Science, 2021)
Candidatus Liberibacter asiaticus (CLas) is the causative agent of Huanglongbing (HLB), which has caused great economic losses to the citrus industry. The molecular mechanism of the host response to CLas in wild citrus germplasm has been reported less. Eighteen weeks after inoculation via grafting, all the CLas-inoculated Chongyi wild mandarin (Citrus reticulata) were positive and showed severe anatomical aberrations, suggesting its susceptibility to HLB. Transcriptomics and metabolomics analyses of leaves, barks, and roots from mock-inoculated (control) and CLas-inoculated seedlings were performed. Comparative transcriptomics identified 3,628, 3,770, and 1,716 differentially expressed genes (DEGs) between CLas-infected and healthy tissues in the leaves, barks, and roots, respectively. The CLas-infected tissues had higher transcripts per kilobase per million values and more genes that reached their maximal expression, suggesting that HLB might cause an overall increase in transcript accumulation. However, HLB-triggered transcriptional alteration showed tissue specificity. In the CLas-infected leaves, many DEGs encoding immune receptors were downregulated. In the CLas-infected barks, nearly all the DEGs involved in signaling and plant-pathogen interaction were upregulated. In the CLas-infected roots, DEGs encoding enzymes or transporters involved in carotenoid biosynthesis and nitrogen metabolism were downregulated. Metabolomics identified 71, 62, and 50 differentially accumulated metabolites (DAMs) in the CLas-infected leaves, barks and roots, respectively. By associating DEGs with DAMs, nitrogen metabolism was the only pathway shared by the three infected tissues and was depressed in the CLas-infected roots. In addition, 26 genes were determined as putative markers of CLas infection, and a hypothesized model for the HLB susceptibility mechanism in Chongyi was proposed. Our study may shed light on investigating the molecular mechanism of the host response to CLas infection in wild citrus germplasm.